Exploring the efficacy and beneficial population of preimplantation genetic testing for aneuploidy start from the oocyte retrieval cycle: a real-world study - Ma, Shujuan; Liao, Jingnan; Zhang, Shuoping; Yang, Xiaoyi; Hocher, Berthold; Tan, Jing; Tan, Yueqiu; Hu, Liang; Gong, Fei; Xie, Pingyuan; Lin, Ge (Journal of translational medicine, 2023)
Preimplantation genetic testing for aneuploidy (PGT-A) is widely used as an embryo selection technique in in vitro fertilization (IVF), but its effectiveness and potential beneficiary populations are unclear. This retrospective cohort study included patients who underwent their first oocyte retrieval cycles at CITIC-Xiangya between January 2016 and November 2019, and the associated fresh and thawed embryo transfer cycles up to November 30, 2020. PGT-A (PGT-A group) and intracytoplasmic sperm injection (ICSI)/IVF (non-PGT-A group) cycles were included. The numbers of oocytes and embryos obtained were unrestricted. In total, 60,580 patients were enrolled, and baseline data were matched between groups using 1:3 propensity score matching. Sensitivity analyses, including propensity score stratification and traditional multivariate logistic regression, were performed on the original unmatched cohort to check the robustness of the overall results. Analyses were stratified by age, body mass index, ovarian reserve/responsiveness, and potential indications to explore benefits in subgroups. The primary outcome was cumulative live birth rate (CLBR). The other outcomes included live birth rate (LBR), pregnancy loss rate, clinical pregnancy rate, pregnancy complications, low birth weight rate, and neonatal malformation rate. In total, 4195 PGT-A users were matched with 10,140 non-PGT-A users. A significant reduction in CLBR was observed in women using PGT-A (27.5% vs. 31.1%; odds ratio (OR) = 0.84, 95% confidence interval (CI) 0.78-0.91; P < 0.001). However, women using PGT-A had higher first-transfer pregnancy (63.9% vs. 46.9%; OR = 2.01, 95% CI 1.81-2.23; P < 0.001) and LBR (52.6% vs. 34.2%, OR = 2.13, 95% CI 1.92-2.36; P < 0.001) rates and lower rates of early miscarriage (12.8% vs. 20.2%; OR = 0.58, 95% CI 0.48-0.70; P < 0.001), preterm birth (8.6% vs 17.3%; P < 0.001), and low birth weight (4.9% vs. 19.3%; P < 0.001). Moreover, subgroup analyses revealed that women aged ≥ 38 years, diagnosed with recurrent pregnancy loss or intrauterine adhesions benefited from PGT-A, with a significant increase in first-transfer LBR without a decrease in CLBR. PGT-A does not increase and decrease CLBR per oocyte retrieval cycle; nonetheless, it is effective in infertile populations with specific indications. PGT-A reduces complications associated with multiple gestations.
Gesehen am 30.09.2024